2018
DOI: 10.1002/vjch.201800043
|View full text |Cite
|
Sign up to set email alerts
|

Natural sulphur‐containing steroids: Origin and biological activities

Abstract: The present review describes the distribution and biological activities of natural sulphur containing steroids (SCS). The structures and predicted biological activities of SCS are presented in the proposed review. Comparatively a small amount of SCS were found in living organisms, but a very large variety of these lipid molecules were found in geological samples and marine sediments. About fifty steroids showed antineoplastic and antipsiomatic activities with a confidence of 72 to 94 %, and some of them can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…A wide variety of chemical structures of steroids and terpenoids was found in extracts of marine sediments, as well as both contemporary and geologically ancient deposits [29,31,[109][110][111][112][113][114]. Aromatic sterols, triterpenoids, and sulfur-containing compounds have been found in marine sediments and crude oil [31][32][33][34][115][116][117][118][119][120].…”
Section: Sulfur-containing Steroids Derived From Marine and Terrestrial Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide variety of chemical structures of steroids and terpenoids was found in extracts of marine sediments, as well as both contemporary and geologically ancient deposits [29,31,[109][110][111][112][113][114]. Aromatic sterols, triterpenoids, and sulfur-containing compounds have been found in marine sediments and crude oil [31][32][33][34][115][116][117][118][119][120].…”
Section: Sulfur-containing Steroids Derived From Marine and Terrestrial Sourcesmentioning
confidence: 99%
“…Until now, there has been no evidence that microorganisms do not participate in the formation of sulfur-containing steroids, but nevertheless, these lipid markers are of great interest for biochemistry, geochemistry, and pharmacology [119][120][121][122]. More than 3000 terpenoids and other lipid molecules have been isolated from sedimentary rocks and marine sediments-this is an established fact [28,30,33,[39][40][41][42][111][112][113][114].…”
Section: Sulfur-containing Steroids Derived From Marine and Terrestrial Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Akihisa and co-workers reported that the fungus Glomerella fusarioides transformed cycloartenol (4) to cycloartane-3,24-dione (31), rare 4α,4β,14α-trimethyl-9β,19-cyclopregnane-3,20-dione (32) and 24,25dihydroxycycloartan-3-one (33) [77]. and cycloartanol (5) are found in a fern oil from the family Polypodiaceae, Polypodium vulgare [78], and 29-nor-cycloartanol (35) and cycloartanol (5) was detected in a flowering plant in the spurge family Euphorbiaceae, Euphorbia balsamifera [79].…”
Section: Cyclopropane Containing Steroids and Triterpenoidsmentioning
confidence: 99%
“…Both sekosterols (14 and 15) isolated from the sponge showed anticancer activity. Topsentisterols B2 (16), B3 (17) and B4 (18), epoxy steroids with the or -hydroxyl group at position 17 were present in the extract of the far eastern sponge of Topsentia sp. [43] Cytotoxic steroids (19)(20)(21), although gibberoepoxysterol (22) showed mild activity, and all these lipids produce the octocoral Sinularia lochmodes collected in the waters of Taiwan.…”
Section: Steroids Bearing 56-epoxy Groupmentioning
confidence: 99%